2005
DOI: 10.1101/gr.3935405
|View full text |Cite
|
Sign up to set email alerts
|

The function and expansion of the Patched- and Hedgehog-related homologs in C. elegans

Abstract: The Hedgehog (Hh) signaling pathway promotes pattern formation and cell proliferation in Drosophila and vertebrates. Hh is a ligand that binds and represses the Patched (Ptc) receptor and thereby releases the latent activity of the multipass membrane protein Smoothened (Smo), which is essential for transducing the Hh signal. In Caenorhabditis elegans, the Hh signaling pathway has undergone considerable divergence. Surprisingly, obvious Smo and Hh homologs are absent whereas PTC, PTC-related (PTR), and a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
137
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 94 publications
(141 citation statements)
references
References 59 publications
4
137
0
Order By: Relevance
“…In summary, all of the observed phenotypes are typical Mlt phenotypes that are also found in many other Mlt mutants. The Mlt phenotypes of qua-1(gk32) are consistent with the RNAi phenotypes that have been observed in large-scale RNAi screens Simmer et al, 2003;Frand et al, 2005;Zugasti et al, 2005). We repeated the qua-1(RNAi) feeding experiment and observed that the worms can have problems during ecdysis at any larval stage when RNAi treatment starts at the L1 stage.…”
Section: Deletion Mutant Qua-1(gk32) Causes Molting Defectssupporting
confidence: 79%
See 2 more Smart Citations
“…In summary, all of the observed phenotypes are typical Mlt phenotypes that are also found in many other Mlt mutants. The Mlt phenotypes of qua-1(gk32) are consistent with the RNAi phenotypes that have been observed in large-scale RNAi screens Simmer et al, 2003;Frand et al, 2005;Zugasti et al, 2005). We repeated the qua-1(RNAi) feeding experiment and observed that the worms can have problems during ecdysis at any larval stage when RNAi treatment starts at the L1 stage.…”
Section: Deletion Mutant Qua-1(gk32) Causes Molting Defectssupporting
confidence: 79%
“…In C. elegans, two patched genes, ptc-1 and ptc-3, as well as 24 patched-related genes exist (Kuwabara et al, 2000). RNAi analysis of these genes revealed that several, no- tably ptc-3, ptr-4, -16, -18, and -23 also cause strong Mlt phenotypes when knocked down (Zugasti et al, 2005). It is feasible that QUA-1 interacts directly with some of these Ptc or Ptr proteins, which may be involved in facilitating secretion of QUA-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, when Hh binds to Ptc, Smo inhibition is released and Hh signal is transduced within the target cell. ptc, found in Drosophila, in nematods (Zugasti et al, 2005) and in vertebrates as well Hahn et al, 1996;Marigo et al, 1996), is itself a target gene of hh signalling.…”
Section: Introductionmentioning
confidence: 99%
“…(29) They are, however, conspicuously absent in C. elegans, probably because its rigid pattern of differentiation can dispense with morphogen gradients. (30) Only some evolutionary remnants, in the form of hedgehog-related genes, remain detectable in the C. elegans genome. (31) The cascade of molecular events leading from Hh processing to signal reception at the target cell are also widely shared among animals.…”
Section: Introductionmentioning
confidence: 99%